Expression of microRNA-155 in thalassemic erythropoiesis - Penglong, Tipparat; Pholngam, Nuttanan; Tehyoh, Nasra; Tansila, Natta; Buncherd, Hansuk; Thanapongpichat, Supinya; Srinoun, Kanitta (PeerJ, 2024)
Background Ineffective erythropoiesis (IE) is the primary cause of anemia and associated pathologies in β-thalassemia. The characterization of IE is imbalance of erythroid proliferation and differentiation, resulting in increased erythroblast proliferation that fails to differentiate and gives rise to enucleate RBCs. MicroRNAs (miRs) are known to play important roles in hematopoiesis. miR-155 is a multifunctional molecule involved in both normal and pathological hematopoiesis, and its upregulation is observed in patients with β-thalassemia/HbE. However, the expression and function of miR-155, especially in β-thalassemia, have not yet been explored. Methods To study miR-155 expression in thalassemia, erythroblast subpopulations, CD45-CD71+Ter-119+ and CD45-CD71−Ter-119+ were collected from βIVSII-654 thalassemic bone marrow. Additionally, a two-phase culture of mouse bone marrow erythroid progenitor cells was performed. Expression of miR-155 and predicted mRNA target genes, c-myc, bach-1 and pu-1, were determined by quantitative reverse transcription (qRT)-polymerase chain reaction (PCR) and normalized to small nucleolar RNA (snoRNA) 202 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), respectively. To investigate the effect of miR-155 expression, erythroblasts were transfected with miR-inhibitor and -mimic in order to elevate and eliminate miR-155 expression, respectively. Erythroid cell differentiation was evaluated by Wright–Giemsa staining and flow cytometry. Results miR-155 was upregulated, both in vivo and in vitro, during erythropoiesis in β-thalassemic mice. Our study revealed that gain- and loss of function of miR-155 were involved in erythroid proliferation and differentiation, and augmented proliferation and differentiation of thalassemic mouse erythroblasts may be associated with miR-155 upregulation. miR-155 upregulation in β-thalassemic mice significantly increased the percentage of basophilic and polychromatic erythroblasts. Conversely, a significant decrease in percentage of basophilic and polychromatic erythroblasts was observed in β-thalassemic mice transfected with anti-miR-155 inhibitor. We also examined the mRNA targets (c-myc, bach-1 and pu-1) of miR-155, which indicated that c-myc is a valid target gene of miR-155 that regulates erythroid differentiation. Conclusion miR-155 regulates IE in β-thalassemia via c-myc expression controlling erythroblast proliferation and differentiation.
Keywords: miR-155; Ineffective erythropoiesis; Thalassemic mice; c-myc